Online service quality and offline service quality on repurchase interest through consumer satisfaction at annisa collection wholesale stores - Eka Dian Puspita; Muhafidhah Novie (Institute of Computer Science (IOCS), 2024)
The aim of this research is to evaluate the influence of online and offline service quality on consumer satisfaction, the impact of online and offline service quality on repurchase interest, and measure the impact of consumer satisfaction on repurchase interest at the Annisa Collection Wholesale Store. Quantitative research methods were used with a sample of 100 customer respondents, selected through purposive sampling techniques. The results of data analysis using the PLS Smart 4.0 application show that the quality of online and offline services has a significant influence on repurchase interest and customer satisfaction. This conclusion provides direction for stores to continue to improve the quality of their services to maintain repurchase interest, customer satisfaction, and support long-term business growth